CD4 trajectory adjusting for dropout among HIV‐positive patients receiving combination antiretroviral therapy in an East African HIV care centre. Issue 2 (14th August 2014) - Kiragga, Agnes N; Lok, Judith J; Musick, Beverly S; Bosch, Ronald J; Mwangi, Ann; Wools‐Kaloustian, Kara K; Yiannoutsos, Constantin T
Abstract : Objective: Estimates of CD4 response to antiretroviral therapy (ART) obtained by averaging data from patients in care, overestimate population CD4 response and treatment program effectiveness because they do not consider data from patients who are deceased or not in care. We use mathematical methods to assess and adjust for this bias based on patient characteristics. Design: We examined data from 25, 261 HIV‐positive patients from the East Africa IeDEA Consortium. Methods: We used inverse probability of censoring weighting (IPCW) to represent patients not in care by patients in care with similar characteristics. We address two questions: What would the median CD4 be "had everyone starting ART remained on observation?" and "were everyone starting ART maintained on treatment?" Results: Routine CD4 count estimates were higher than adjusted estimates even under the best‐case scenario of maintaining all patients on treatment. Two years after starting ART, differences between estimates diverged from 30 cells/µL, assuming similar mortality and treatment access among dropouts as patients in care, to over 100 cells/µL assuming 20% lower survival and 50% lower treatment access among dropouts. When considering only patients in care, the proportion of patients with CD4 above 350 cells/µL was 50% adjusted to below 30% when accounting for patients not in care. One‐year mortality diverged 6–14% from the naïve estimates depending on assumptions about access to care among lost patients. Conclusions: Ignoring mortality and loss to care results in over‐estimation of ART response for patients starting treatment and exaggerates the efficacy of treatment programs administering it.